Cost and Satisfaction Trends in Swedish Elderly Home Care. (November 2016) - Kazemi, Ali; Kajonius, Petri J.
There is a widespread belief among the public and policy makers that quality of care in terms of user satisfaction can be improved with increased spending. However, recent research indicates that structural resources (e.g., budget per elderly) in elderly home care do not predict quality of care in terms of older persons' satisfaction with care. In the present study, we analyzed the longitudinal trends in costs and perceived quality of care across 3 years using nationwide data in Swedish elderly home care. The results showed that although costs have been steadily increasing, perceived quality of interpersonal treatment in care has remained at the same level. An important implication is that future research and policy efforts to improve quality should more directly target the mechanisms generating satisfaction.